2021
DOI: 10.1016/j.isci.2021.102094
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-up of microbial electrosynthesis with multiple electrodes for in situ production of hydrogen peroxide

Abstract: Up-scaled microbial electrosynthesis with multiple electrodes to synthesize H 2 O 2 The H 2 O 2 yield was higher than that of laboratoryscale systems using graphite cathode Energy consumption was lower than that of laboratory-scale (bio) electrochemical systems Systematic evaluation of the influence of operating parameters on H 2 O 2 production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…43,44 Interface engineering is regarded as one potent pathway to expedite catalytic kinetics because multidoped hybrid nanostructures have synergistic effects on the electrocatalytic activity compared to their single-component counterparts. [45][46][47][48][49] Electronic modulation can be achieved by constructing heterostructures, and their unique electron-recongured nanointerfaces accelerate electrode performance by regulating the adsorption of the reactants and electronic interactions at the interface. 50,51 It is desirable to fabricate freestanding electrodes with high catalyst loading, abundant active sites, and superior activity by interfacial engineering.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Interface engineering is regarded as one potent pathway to expedite catalytic kinetics because multidoped hybrid nanostructures have synergistic effects on the electrocatalytic activity compared to their single-component counterparts. [45][46][47][48][49] Electronic modulation can be achieved by constructing heterostructures, and their unique electron-recongured nanointerfaces accelerate electrode performance by regulating the adsorption of the reactants and electronic interactions at the interface. 50,51 It is desirable to fabricate freestanding electrodes with high catalyst loading, abundant active sites, and superior activity by interfacial engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid increase of pH in the divided cell directed that the consumption rate of H + at the cathode for the synthesis of H 2 O 2 was faster than the generation rate at the anode. 55 These findings suggest that the alkaline environment is important for efficient H 2 O 2 production. It seems that 2e − selectivity for the ORR relies on the pH of the electrolyte, which is consistent with the previous findings.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…12 after 10 min electrolysis in the divided cell, while it decreased to <2 in the undivided cell, which remains almost constant after 10 min electrolysis. The rapid increase of pH in the divided cell directed that the consumption rate of H + at the cathode for the synthesis of H 2 O 2 was faster than the generation rate at the anode . These findings suggest that the alkaline environment is important for efficient H 2 O 2 production.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the in-situ electrochemical synthesis of H 2 O 2 from 2e − oxygen reduction reaction (ORR) has attracted intensive attention in labs and industries [17]. Although substantial efforts have been invested in catalyst preparation and cathode fabrication [18][19][20], few studies have shown the practical utility of H 2 O 2 -AOPs at device levels. Low H 2 O 2 dosage cannot meet the treatment requirements of high COD wastewater, while excessive H 2 O 2 introduction needs post-treatment of the effluent [4].…”
Section: Introductionmentioning
confidence: 99%